The Long Shadow of Violence: Legacies of Civil Wars and Support for Terrorism in the Basque Country - Criado, Henar (Terrorism and political violence, 2024)
This article analyses how events of political violence in the distant past affect the outbreak of terrorism in the present. Civil wars leave a legacy of distrust that can persist through generations, paving the way to violent responses to perceived threats. We claim that part of the explanation for the counterintuitive terrorism phenomenon in a prosperous and relatively egalitarian region such as the Basque Country (and, potentially, other cases of terrorism) lies in the legacies of political violence in the distant past. Those communities where support for Carlism, one of the warring factions in nineteenth-century civil wars, was strong, were more likely to support terrorism a century later. The article also shows that the transmission of these legacies was robust in communities that have remained largely isolated in the century that separates the civil war from the terrorism of the 1970s.